Цілеспрямований пошук біологічно активних речовин на основі п’ятичленних гетероциклів та споріднених гетероциклічних систем для лікування серцево-судинних захворювань - Драпак, І. В.; Драпак, И. В.; Drapak, I. V. (Запорізький державний медичний університет, 2020)
Дисертаційна робота є комплексним фундаментальним дослідженням, яке присвячене цілеспрямованому пошуку на основі віртуального скринінгу та раціонального дизайну, синтезу, вивченню фізико-хімічних, фармакологічних властивостей біологічно активних речовин на основі п’ятичлених гетероциклів та споріднених гетероциклічних систем з метою подальшого впровадження в промислове виробництво та медичну практику нових речовин для лікування серцево-судинних захворювань. На основі прогнозування активності, токсичності, молекулярних дескрипторів, оцінки аффінності, QSAR-аналізу, фармакофорного моделювання похідних п’ятичленних гетероциклів обрано перспективні об’єкти для цілеспрямованого синтезу та фармакологічних досліджень як потенційні серцево-судинні агенти. Ідентиіфіковано сполуки-лідери: [3-аліл-4-(41-метоксифеніл)-3Н-тіазол-2-іліден]-(32-трифлуорометил-феніл)аміну гідробромід (Кардіазол) та N-(5-метил-[1,3,4]тіадіазол-2-іл)-пропіонамід (Урокарб). Для Кардіазолу встановлена кардіопротекторна, анальгетична, протизапальна, гіполіпідемічна, антигіпоксична та антиоксидантна активності. Урокарб рекомендований як потенційний діуретик. Проведено дослідження щодо масштабування синтезу Кардіазолу та Урокарбу в промислових умовах ПАТ «Фармак». Розроблено та валідовано аналітичні та біоаналітичні методики визначення Кардіазолу та Урокарбу. Диссертационная работа представляет собой комплексное фундаментальное исследование, посвященное целенаправленному поиску на основе виртуального скрининга и рационального дизайна, синтезу, изучению физико-химических, фармакологических свойств биологически активных веществ на основе пятичленных гетероциклов и родственных гетероциклических систем с целью дальнейшего внедрения в промышленное производство и медицинскую практику новых веществ для лечения сердечно-сосудистых заболеваний. На основе прогнозирования активности, токсичности, молекулярных дескрипторов, оценки аффинности QSAR-анализа, фармакофорного моделирования производных пятичленных гетероциклов выбрано перспективные объекты для целенаправленного синтеза и фармакологических исследований как потенциальные сердечно-сосудистые агенты. Идентифицированно соединения-лидеры: [3-аллил-4(41-метоксифенил)-3Н-тиазол-2-илиден]-(32-трифлуоро-метил-фенил)амина гидро-бромид (Кардиазол) и N-(5-метил[1,3,4-тиадиазол-2-ил)-пропионамид (Урокарб). Для Кардиазола установлена кардиопротекторная, анальгетическая, противовоспалительная, гиполипидемическая, антигипоксическая и антиоксидантная активности. Урокарб рекомендован как потенциальный диуретик. Проведено исследование масштабирования синтеза Кардиазола и Урокарба в промышленных условиях ОАО «Фармак». Разработаны и валидированы аналитические и биоаналитические методики определения Кардиазола и Урокарба. The dissertation is a comprehensive fundamental research, dedicated to purposeful research on the virtual screening and rational design, synthesis, study of physicochemical properties and pharmacological activity of biologically active substances based on five-membered heterocycles and related heterocyclic systems for the treatment of cardiovascular diseases. A library of compounds has been formed based on diversified functionalized five-membered heterocycles (thiazole, thiazolidine, thiadiazole, pyrazole, thiophene, triazole) and some of their fused derivatives. Virtual screening based on prediction of biological activity/toxicity was performed. Molecular descriptors (electronic, electrostatic, geometric, steric, topological and energetic) of virtual library compounds were calculated and drug-like parameters were evaluated. Compounds with predicted unsatisfactory parameters and toxicity level were excluded from further analysis. The next step was the molecular docking. Groups of substances with high affinity to biotargets associated with cardiovascular drugs action have been identified. The prognostic values of the parameters of the tested compounds have become a theoretical platform for the synthesis of potential agents for the treatment of cardiovascular diseases. As a result of screening studies, the structure of the virtual library was optimized and sub-libraries of compounds were outlined for further synthetic and pharmacological studies, using molecular hybridization approaches. On the basis of preliminary calculations and according to the stages of the study design, the pharmacological activity of the synthesized compounds was screened. Screening studies included an analysis of the effects of drug-specific drugs for the treatment of cardiovascular diseases: the active compounds were identifi ed and the basic patterns of structure-activity (cardioprotective, antihypertensive, antioxidant, and diuretic) that were used for purposeful search for compounds were identified. Based on calculated molecular descriptors and values of pharmacological activity, the analysis of the quantitative relationship structure - activity was performed. The resulting QSAR models were used to predict the corresponding activity of the molecules. Conducted pharmacophore modeling allowed to obtain pharmacophore models of cardioprotective, diuretic, antihypertensive activity. The obtained pharmacophore models are used for in silico screening and purposeful search for potential cardioprotectors, diuretics, and antihypertensive agents. Pharmacophore modeling allows to select structures of promising molecules for synthetic studies. Based on the analysis of screening results (molecular docking, pharmacophore modeling, QSAR, etc.), structure optimization and purposeful synthesis of the predicted most active derivatives of functionalized five-membered heterocycles were carried out. New 2-arylimino-1,3-thiazole derivatives were obtained from thioureas and bromo-4-R1-acetophenones. New N1-(4-(R1-phenyl)-1,3-thiazol-2-yl)-N1-(R-phenyl) acetamides were obtained by acetylation of thiourea derivatives. The synthesized compounds possesed high level of cardioprotective and antihypertensive activities. Synthesis of 2-(5-amino-1,3,4-thiadiazol-2-yl-sulfanyl)-1-phenylethanones was accomplished by the interaction of 2-amino-5-mercapto-1,3,4-thiadiazole and α-bromoacetophenones; 2-amino-5-benzylsulfanyl-1,3,4-thiadiazoles - by the reaction of 2-amino-5-mercapto-1,3,4-thiadiazole and benzyl chlorides. The N-(1,3,4-thiadiazol-2-yl) substituted acid amines of the alkanecarboxylic acid series are obtained in reaction of 2-amino-5-alkyl-1,3,4-thiadiazole with the corresponding acyl chlorides. Studies of diuretic activity have shown that all synthesized compounds have eqiual or higher activity levels compare to reference drugs. Lead-compounds - [3-allyl-4-(41-methoxyphenyl)-3H-thiazol-2-ylidene]-(32-trifl uoromethylphenyl)amine hydrobromide (Cardiazole) and N-(5-methyl-[1,3,4] thiadiazol-2-yl)-propionamide (Urocarb) have been identifi ed. Cardiazole has been multitargeted (based on docking studies) and experimentally confirmed polypharmacological activity: cardioprotective, antioxidant, hypolipidemic, antiinflammatory, analgesic, antihypoxic, hypotensive and low toxicity. Urocarb as a potential diuretic drug exceeds the activity of hydrochlorothiazide and acetazolamide (1.6 and 1.8 times, respectively). Also, the antioxidant and anti-inflammatory effects as well as satisfactory toxicological profi le have been established for Urocarb. Research on the large-scale synthesis methods for Cardiazole and Urocarb has been carried out; the optimal technological parameters have been established. The block diagram of industrial synthesis has been developed. The modified technology has been tested under the industrial conditions of “Pharmak”. Analytical and bioanalytical methods for the determination of Cardiazole and Urocarb have been developed and validated.
Целенаправленный поиск биологически активных веществ на основе пятичленных гетероциклов и родственных гетероциклических систем для лечения сердечно-сосудистых заболеваний
Purposeful search for biologically active substances based on five-membered heterocycles and related heterocyclic systems for the treatment of cardiovascular disease
Keywords: п’ятичленні гетероцикли; серцево-судинні захворювання; віртуальний скринінг; синтез; фармакологічна активність; методи контролю якості; біоаналітичні дослідження; пятичленные гетероциклы; сердечно-сосудистые заболевания; виртуальный скрининг; фармакологическая активность; методы контроля качества; биоаналитические исследования; five-membered heterocycles; cardiovascular diseases; virtual screening; synthesis; pharmacological activity; quality control methods; bioanalytical studies